Sensory function in the faces of patients with facial palsy: A prospective observational study using quantitative sensory testing - Volk, Gerd Fabian; Döhler, Marianna; Klinger, Carsten M.; Weiss, Thomas; Guntinas-Lichius, Orlando (Frontiers in Pain Research, 2022)
Objectives/Hypothesis: To determinate the sensory function of both sides of the face in patients with acute or chronic facial palsy. Study Design: Prospective observational study. Methods: The standardized quantitative sensory testing (QST) protocol of the German Research Network on Neuropathic Pain (DFNS) including thermal or mechanical nature stimuli (touch, pain, vibration, and pressure) was used to investigate somatosensory function in the face of the patients. As patient reported outcome measures for the assessment of a disturbed facial comfort or facial pain, the facial Clinimetric Evaluation Scale (FaCE) Facial Comfort Subscale and the 36-Item Short Form Survey (SF-36) pain subdomain were used Results: 29 patients (22 female, median age: 48 years; 7 acute palsy; 22 chronic palsy; House-Brackmann grade II to VI) were included. The median FaCE Facial Comfort Subscale score and the median SF-36 pain subdomain were 50 and 100, respectively. Most patients had on the individual level a normal sensory function in all or most tests. On average, the frequencies for all parameters were not different between paretic side and the contralateral side (all p>0.05). When compared with healthy controls of the DFNS reference database using the z-scores, there was also no difference between the paretic side and the contralateral side (all p>0.05). Furthermore, there were no differences between patients with acute versus chronic facial palsy (all p>0.05). The FaCE Facial Comfort Subscale score and the SF-36 pain subdomain score did not correlate to the QST parameters (all p>0.05). Conclusion: Patients with acute or chronic unilateral peripheral facial palsy had a normal sensory function on the paretic and on the contralateral side compared to reference values of healthy controls as well as no significant side difference. The frequently felt numbness in the affected hemiface is not related to a peripheral sensory disorder. It is most likely a manifestation of an unsolved cortical somatosensory-motor mismatch.